E-FILING IN TAX: IMPROVING COMPLIANCE THROUGH DIGITAL INNOVATION - Andi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
An online tax reporting method that allows taxpayers to submit their tax reports more quickly, safely, and accurately through the internet is called e-filing. The implementation of e-filing aims to improve tax compliance by simplifying the reporting process, improving data protection, and providing support and education for taxpayers. The study conducted based on this literature research uses the literature research method. The findings of this study show that the implementation of e-filing is a powerful strategy in improving tax compliance. By utilising technology to simplify the reporting process, improve data protection, and provide adequate education and support, e-filing not only improves administrative efficiency but also builds taxpayer trust and compliance. Therefore, e-filing can be viewed as an important tool in sustainable and comprehensive tax reform.